Characterization of the gut microbiota of migratory passerines during stopover along the northern coast of the Gulf of Mexico. (4th April 2016) - Lewis, William B.; Moore, Frank R.; Wang, Shiao
Abstract : Although the gut microbiota is known to provide many beneficial functions to animal hosts, such as aiding in digestion, fat metabolism, and immune function, relatively little is known about the gut microbiota of passerines. Gut microbes may have both beneficial and detrimental impacts on the fitness of migratory passerines; however physiological and morphological changes associated with prolonged migratory flight may cause disruptions of the stable microbiota and potentially a loss of function. Fecal samples were collected from Swainson's thrushes Catharus ustulatus and gray catbirds Dumetella carolinensis immediately after crossing the Gulf of Mexico during spring migration and before crossing during fall, and microbiota communities were analyzed using next‐generation sequencing. Microbiota communities were generally dominated by Firmicutes and Proteobacteria, with potential pathogens as well as potentially beneficial bacteria identified in all birds. Energetic condition of migrants was not significantly related to overall microbiota community structure though it cannot be conclusively stated that migratory flight does not impact the microbiota. Spring and fall migrants showed clear differences in microbiota communities, indicating that environmental factors influence the gut microbiota of these species more than host genetics.